Dielectric relaxation induced by oxygen vacancies in Na_0.5Bi_0.5TiO_3 ceramics - V. M. Sidak; M. P. Trubitsyn; T. V. Panchenko (Condensed Matter Physics, 2022)
Dielectric permittivity was studied in ceramics of relaxor ferroelectric bismuth-sodium titanate Na_0.5Bi_0.5TiO_3. The measurements were performed on as sintered and heat treated in vacuum samples. The diffuse dielectric anomalies associated with the structural phase transitions were observed in as sintered samples. The intense peak of permittivity (ε_max ∼ 104) appeared after heat treating in vacuum. The anomaly of ε(T) was contributed by slow polarization processes (f < 10 kHz) and was non-stable, vanishing on heating in air up to ∼ 800 K. Temperature and frequency dependencies of ε were described by using Cole-Cole model with accounting thermally stimulated decay of the non-stable polarization. It is supposed that the dielectric anomaly is determined by space charge polarization mechanism. Oxygen vacancies VO•• and electrons localized on titanium ions Ti'_Ti are assumed to be responsible for the phenomenon observed.